Concerted Divergence after Gene Duplication in Polycomb Repressive Complexes - Qiu, Yichun (Plant Physiol, 2017)
Duplicated genes are a major contributor to genome evolution and phenotypic novelty. There are multiple possible evolutionary fates of duplicated genes. Here, we provide an example of concerted divergence of simultaneously duplicated genes whose products function in the same complex. We studied POLYCOMB REPRESSIVE COMPLEX2 (PRC2) in Brassicaceae. The VERNALIZATION (VRN)-PRC2 complex contains VRN2 and SWINGER (SWN), and both genes were duplicated during a whole-genome duplication to generate FERTILIZATION INDEPENDENT SEED2 (FIS2) and MEDEA (MEA), which function in the Brassicaceae-specific FIS-PRC2 complex that regulates seed development. We examined the expression of FIS2, MEA, and their paralogs, compared their cytosine and histone methylation patterns, and analyzed the sequence evolution of the genes. We found that FIS2 and MEA have reproductive-specific expression patterns that are correlated and derived from the broadly expressed VRN2 and SWN in outgroup species. In vegetative tissues of Arabidopsis (Arabidopsis thaliana), repressive methylation marks are enriched in FIS2 and MEA, whereas active marks are associated with their paralogs. We detected comparable accelerated amino acid substitution rates in FIS2 and MEA but not in their paralogs. We also show divergence patterns of the PRC2-associated VERNALIZATION5/VIN3-LIKE2 that are similar to FIS2 and MEA. These lines of evidence indicate that FIS2 and MEA have diverged in concert, resulting in functional divergence of the PRC2 complexes in Brassicaceae. This type of concerted divergence is a previously unreported fate of duplicated genes. In addition, the Brassicaceae-specific FIS-PRC2 complex modified the regulatory pathways in female gametophyte and seed development.